2020
DOI: 10.1038/s41467-020-16871-9
|View full text |Cite
|
Sign up to set email alerts
|

Z3-vestigial nematic order due to superconducting fluctuations in the doped topological insulators NbxBi2Se3 and CuxBi2Se3

Abstract: A state of matter with a multi-component order parameter can give rise to vestigial order. In the vestigial phase, the primary order is only partially melted, leaving a remaining symmetry breaking behind, an effect driven by strong classical or quantum fluctuations. Vestigial states due to primary spin and charge-density-wave order have been discussed in iron-based and cuprate materials. Here we present the observation of a partially melted superconductivity in which pairing fluctuations condense at a separate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 44 publications
4
29
1
Order By: Relevance
“…report a slight expansion in c on Nb doping, but do not report the estimated standard deviation and Cho et al 20 report a c lattice parameter of 28.4633(7) Å, which is much smaller than what we and Wang et al 19 find for pure Bi 2 Se 3 . Our previous work on Li 1-x Fe 1+x As samples showed that trends in lattice parameters arising from very small compositional changes could only be monitored by synchrotron radiation 27 .…”
Section: Resultscontrasting
confidence: 76%
See 4 more Smart Citations
“…report a slight expansion in c on Nb doping, but do not report the estimated standard deviation and Cho et al 20 report a c lattice parameter of 28.4633(7) Å, which is much smaller than what we and Wang et al 19 find for pure Bi 2 Se 3 . Our previous work on Li 1-x Fe 1+x As samples showed that trends in lattice parameters arising from very small compositional changes could only be monitored by synchrotron radiation 27 .…”
Section: Resultscontrasting
confidence: 76%
“…In this paper and particularly in the supporting information we describe the structure in detail and show how (BiSe) 1.10 NbSe 2 compares with related misfit layered chalcogenides. This misfit phase corresponds to the peaks previously assigned to the BiNbSe 3 impurity 18 (which is of fairly similar composition) by Kobayashi et al 11 and by Cho et al 20 We observe that the amount of the phase present with the Bi 2 Se 3 structure (assumed to be the superconducting phase Nb x Bi 2 Se 3 in the literature 11,12,17,19,20,[22][23][24][25][26] , including very recent literature 19,20,24,25 ) in the samples decreases with increasing Nb content in the synthesis mixture and completely vanishes for x = 0.50 while the superconducting volume fraction of the sample is directly proportional to the Nb content of the sample. In addition we do not observe, with synchrotron resolution, a measurable caxis expansion of the Bi 2 Se 3 -structure phase upon Nb doping, suggesting that it is pure and undoped Bi 2 Se 3 .…”
supporting
confidence: 81%
See 3 more Smart Citations